Assessment of the user's dependability-relevant abilities for enhanced human-technology interaction - Wagner, Achim; Bartolein, Christian; Jipp, Meike; Badreddin, Essameddin (Proceedings of the Human Factors and Ergonomics Society 52nd annual meeting, 2008)
Abstract: The dependability of human-technology interaction can significantly be enhanced if the operators' errors occurring due to a mismatch of the system's demands and the actually present (cognitive) abilities of the operator are reduced. This is why, an approach is introduced on which basis a technical system can automatically assess its user's ability level and reconfigure itself or its interface accordingly. The proposed automated assessment is based on the task's difficulty, the user's reaction towards the task he/she is executing with the system at hand, and a logarithmic sigmoid function. Simulation experiments are presented and first results discussed, demonstrating that the proposed realization of the automated assessment allows reliably estimating the individual levels of the dependability-relevant user abilities